Association between 45T/G Polymorphism of Adiponectin Gene and Coronary Artery Disease in an Iranian Population. (2011) - Sabouri, Somaye; Ghayour Mobarhan, Majid; Moohebati, Mohsen; Hassani, Mitra; Kassaeian, Jamal; Tatari, Farnoosh; Mahmoodi-kordi, Fatemeh; Esmaeili, Habib A.; Tavallaie, Shima; Paydar, Roghayeh; Sahebkar, Amirhossein; Tehrani, Shahireh Omidvar; et al.
Abstract : A single nucleotide polymorphism (SNP) in the adiponectin gene, 45T/G, has been reported in relation to a number of metabolic disorders, including obesity, insulin resistance, and diabetes. However, previous studies on the association between this SNP and the presence of coronary artery disease (CAD) have been few, with no report from Iranian subjects. The present study set out to investigate the association between this SNP and CAD in an Iranian population. Among 464 patients (age: 18–75 years), recruited from individuals who underwent coronary angiography, 135 patients had less than 50% reduction of coronary artery diameter and were classified as the CAD- group and 329 patients had more than 50% reduction of coronary artery diameter and were classified as the CAD+ group. The last group was divided into single-vessel disease (n = 86), two-vessel disease (n = 111), and three-vessel disease (n = 132). Healthy subjects (n = 106) who did not have any history of heart diseases were also recruited as the control group. All subjects were genotyped for the 45T/G polymorphism using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique. A significantly higher frequency of the TG genotype and G allele, which was paralleled by a lower frequency of the TT genotype and T allele, was observed in both CAD+ and CAD- patients when compared with the control group ( p ≤ 0.001). There was no significant difference in the genotype distribution and allele frequencies between CAD+ and CAD- patients, and also between different subgroups of patients based on the number of stenosed vessels ( p > 0.05). Our findings indicate that the presence of the G allele at the position +45 of the adiponectin gene may be associated with the risk of CAD in our study population. While we found no significant difference in the genotype distribution and allele frequencies between patients with angiography+ and angiography, this may be because the 50% stenosis cut-off does not discriminate sufficiently between individuals with and without significant coronary disease.